Developing a White anti-racism identity - Berg, Kathryn K.; Simon, Shirley R. (Groupwork, 2013)
This paper describes and assesses a seven session psycho-educational group on anti-racism identity development for White European-American undergraduate students at a midwestern U.S. university. It is predicated on the premise that Whiteness can simultaneously privilege and harm White people, and that White students have the potential to become personally invested in the challenging of systematic racism. It is also based on the idea that a group structure presents an ideal format for addressing this topic. Peer support, a safe environment, and information are requisites for facilitating personal exploration of this sensitive subject. A group model for addressing this topic is presented and assessed. Key considerations, essential elements, strengths and weaknesses, suggestions for replication and further research are discussed.